2022
DOI: 10.17645/mac.v10i4.5690
|View full text |Cite
|
Sign up to set email alerts
|

How Right-Wing Populist Comments Affect Online Deliberation on News Media Facebook Pages

Abstract: Right-wing populist user comments on social media are said to impair online deliberation. Right-wing populism’s anti-pluralist and conflict-centered message might hinder deliberative debates, which are characterized by reciprocity, arguments, sourcing, politeness, and civility. Although right-wing populism has been found to foster user interaction on social media, few empirical studies have examined its impact on the scope and deliberative quality of user debates. This study focuses on debates on 10 Facebook p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Theoretically, comment sections were envisioned as platforms for rational and respectful exchange of diverse viewpoints, where the power of the better argument prevails. Scholars hoped that user comments would enhance inclusivity, participation and deliberation in the public discourse [18]. They were seen as these spaces providing additional information, introducing journalistic content to a diverse pool of citizen opinions and broadening readers' interpretations of issues and events [19].…”
Section: The Lost Promise Of Online Deliberationmentioning
confidence: 99%
“…Theoretically, comment sections were envisioned as platforms for rational and respectful exchange of diverse viewpoints, where the power of the better argument prevails. Scholars hoped that user comments would enhance inclusivity, participation and deliberation in the public discourse [18]. They were seen as these spaces providing additional information, introducing journalistic content to a diverse pool of citizen opinions and broadening readers' interpretations of issues and events [19].…”
Section: The Lost Promise Of Online Deliberationmentioning
confidence: 99%
“…To recap, while nativism prominently manifests itself as anti-immigration positions, it can also take on other forms and attach itself for instance to economic, cultural, or religious issues to express concern for in-group “homogeneity.” To capture these different facets of nativist ideas, we establish a dictionary starting with Guia’s (2016) operationalization, but also draw on previous dictionaries that measure adjacent concepts in media discourse (Thiele, 2019) or anti-immigrant sentiments and Islamophobia in party manifestos (Kortmann et al, 2019). To apply our dictionary to all countries, we only adjust these expressions in cases where patterns refer, for example, to “the [COUNTRY’S] culture and traditions.” Based on our pre-existing knowledge of election campaigns and the RR’s use of nativist language, we created different versions of the dictionary and manually tested the resulting identification of nativist statements.…”
Section: Empirical Approach and Case Selectionmentioning
confidence: 99%
“…Hameleers finds that radical right-wing populist messages can play a role in priming support. Thiele and Turnšek (2022) examine the quality of online deliberation when populist messages are present. Analyzing comments on Facebook pages from Austrian and Slovenian mass media in 2015-2016, they found that right-wing populist comments increase the number of replies, but ultimately decrease the quality of deliberation.…”
Section: Contributionsmentioning
confidence: 99%